Some equilibrium strategies in the games on the unit square - Sūdžiūtė, D.; Gorelik, L. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Суджюте, Л. Горелик. Некоторые уравновешенные пары стратегий в играх на единичном квадратеD. Sūdžiūtė, L. Gorelik. Kai kurios pusiausvyros strategijos lošimuose vienetiniame kvadrate